Internal branding with corporate ethical values and corporate social responsibility: The case of the life insurance industry in Taiwan - C-S. Lai; K-T. Hsu (South African Journal of Business Management, 2015)
The purpose of this study is to identify the extent to which corporate ethical values and employee-oriented CSR can be employed as business levers of internal branding for the life insurance industry. Our results indicate that the impact ofcorporate ethical values on internal branding benefits is fully mediated by knowledge dissemination, and that the impact of employee-based CSR on internal branding benefits is partially mediated by knowledge dissemination. Therefore, forlife insurance companies, employee-oriented CSR can be considered an independent lever of internal branding and can be conducted without other auxiliary initiatives to induce internal branding benefits.
Keywords: 650